2021
DOI: 10.1108/emjb-02-2021-0020
|View full text |Cite
|
Sign up to set email alerts
|

Theory of planned behaviour and boycotting: the moderating role of socio-political control and demographics

Abstract: PurposeThis study examines the predictive ability of the theory of planned behaviour (TPB) to explain consumers' intentions to boycott “unethical”super market (S/M) products. It aims to expand the TPB by investigating the moderating role of politics and selected demographics in the formation process of behavioural intentions.Design/methodology/approachA survey with personal interviews was conducted in the urban area of Thessaloniki, Greece. The two-stage area, in combination with the stratified sampling, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 60 publications
0
32
1
Order By: Relevance
“…, 2012; Stolle et al. , 2005), a few recent studies have found the opposite, suggesting that men show greater involvement (Delistavrou, 2021; Fernandes, 2020). In contrast, while Krishna and Kim (2019) found a nonsignificant result of gender differences, Neilson (2010) contended that gender is a lesser prominent factor in explaining consumer boycotts.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…, 2012; Stolle et al. , 2005), a few recent studies have found the opposite, suggesting that men show greater involvement (Delistavrou, 2021; Fernandes, 2020). In contrast, while Krishna and Kim (2019) found a nonsignificant result of gender differences, Neilson (2010) contended that gender is a lesser prominent factor in explaining consumer boycotts.…”
Section: Introductionmentioning
confidence: 91%
“…These include consumers' perceptions of a firm's egregiousness toward the factory closings in terms of a cost-benefit approach (Klein et al, 2004), consumer animosity to the specific country drawn from the animosity model (Ettenson and Klein, 2005) or consumer animosity to a locality from the perspective of socio-psychological theories (Coss ıo-Silva et al, 2019). In relation to the effects of consumers' psychological and motivational factors, prior studies applied TPB and demonstrated how attitudes, subjective norms and perceived behavioral control increase the boycott intention (Delistavrou, 2021;Delistavrou et al, 2020;Farah and Newman, 2010). Yet, Lavorata (2014) found an unanticipated result, suggesting that boycott intention enhanced by subjective norms and perceived behavioral control is negatively linked to actual boycott behavior.…”
Section: Consumer Boycott Researchmentioning
confidence: 99%
See 3 more Smart Citations